The Mechanisms of Antibiotic Resistance in Bacteria of The Genus Campylobacter - V. V. Stetsenko; N. R. Efimochkina (Антибиотики и Химиотерапия)
Antibiotic resistance of bacteria that contaminate raw food products is currently one of the most acute public health problems. The widespread use of antibiotics for therapeutic or prophylactic purposes in veterinary medicine and as growth promoters for farm animals and poultry creates the conditions for selective pressure on bacterial populations, leading to their adaptation and dissemination of antibiotic- resistant strains of emergent foodborne pathogens, including bacteria of the genus Campylobacter. According to the WHO, campylobacteriosis gastroenteritis retains its leading position among the acute foodborne infections. The article analyzes the features of genetic transformation and formation of resistance of Campylobacter bacteria to several classes of antimicrobial drugs, most commonly used in medicine and veterinary. It is shown that Campylobacter spp. have multiple ways to enhance resistance, which include horizontal DNA transfer (through the mechanism of natural transformation), plasmid transfer of resistance genes and chromosomal mutations. The article presents the data on specific mechanisms of Campylobacter jejuni antibiotic resistance to fluoroquinolones, tetracyclines, aminoglycosides, and macrolides. It is shown that the expression of resistance in Campylobacter spp. is the most pronounced in relation to tetracyclines, which in recent years has led to a rapid increase to 61—87% of the proportion of tetracycline-resistant strains among the populations of campylobacters, contaminating food products. The analysis of data confirming the transfer of resistance genes and total resistance of Ñ.jejuni to fluoroquinolones, which was formed as a result of prolonged exposure to sublethal doses of these drugs, was carried out. The tendency of Ñ.jejuni to form resistance to macrolides, primarily to erythromycin, caused not only by chromosomal mutations, but also by the presence of transmissive plasmid resistance, is now considered as a serious threat to public health. The search for new informative antibiotic resistance markers of Campylobacter spp. will allow making prognostic assessment of the risk of formation of resistance of campylobacteriosis pathogens to the most frequently used antimicrobial agents.